FSKTM on-line room booking system / Ser Ah Ming - Ser, Ah Ming (2000)
The purpose of this report is to document the essential information and need to develop this system that is On-line Room Booking System. This report is mainly divided into 6 chapter. A brief synopsis of each chip is as follows: